Analisis Kualitas Tes Hasil Belajar Matematika Buatan Guru di SMP Negeri 4 Gorontalo - Farianti A. Tiban; Novianita Achmad; Siti Zakiyah (Department of Mathematics, Universitas Negeri Gorontalo, 2021)
This research was conducted with the aim of knowing the quality of teacher-made tests, this study was conducted at SMP Negeri 4 Gorontalo in the 2020/2021 school year. Subjects in the study in the form of odd semester final exam tests of mathematics subjects given to students along with the answers/responses of students to the tests given. The student in question is a class VIII student with a total of 266 students. The quality of the teacher's math tests is analyzed based on the difficulty level, differentiating power, and function of the extractor. The results showed that the quality of mathematics tests made by teachers in State Junior High School 4 Gorontalo as many as 25 items with objective forms can be categorized as less good. This is indicated by the three indicators used to fall into the category of less good.